Pengaruh Kombinasi Nutrisi AB Mix dan Pupuk Organik Cair Daun Turi Terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca Sativa L.) Pada Hidroponik Sistem Sumbu - Dinda Lutfiah; Nikmah Nikmah; Linda Bachrun (Fakultas Pertanian Universitas Borobudur, 2023)
This study aims to determine the effect of POC, AB Mix and the interaction of POC turi leaves and AB Mix on the growth and yield of green lettuce plants (Lactuca sativa L.) with hydroponic cultivation of wick systems. The research was carried out on Jl Raya Setu No. 92, West Cikarang and began from August to September 2022. The design used is a factorial Group Random Design (RAK) with 2 factors and 3 repeats. The first factor of POC concentration of turi leaves consists of: T1 (15 ml), T2 (30 ml) and T3 (45), and the second factor AB Mix nutrition consisting of M1 (100 ppm), M2 (300 ppm) and M3 (500 ppm). The sample was determined by 4 plants per treatment, so that a total of (3x3x3x4) 108 plants. The observed data were further tested using the Duncan Multiple Range Test (DMRT) at the level of 5%. The results showed that the application of turi leaf POC and AB Mix had a significant influence on stem diameter and wet weight of plants, and did not differ significantly in other parameters. T1M3 treatment (15 ml poc turi leaves and AB Mix 500 ppm) tends to give the best results on the growth of green lettuce plants.